Mechanisms and Dynamics of Parent–School Collaboration in Cultivating Qur'anic Morals: A Case Study at TAUD SaQu Zidna Ilma - Syafa'atus Syarifah; Imam Kanafi (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
Cultivating Qur'anic morals in early childhood requires sustained collaboration between schools and families to ensure consistent moral habituation across learning environments. This study aims to analyze the implementation and dynamics of parent–school collaboration in cultivating Qur'anic morals through the At-Tibyan Curriculum at TAUD SaQu Zidna Ilma. A qualitative case study design was employed using semi-structured interviews, non-participant observation, and document analysis. Data were analyzed using the Miles model through four stages: data collection, data condensation, data display, and conclusion drawing and verification. The findings reveal that collaboration is built through continuous communication, shared understanding developed through parenting programs, collaborative monitoring using adab journals and mutaba'ah books, and a clear division of roles between schools and families. The dynamics of collaboration are influenced by parental involvement, teacher responsiveness, monitoring systems, and institutional support. This study demonstrates that the effective cultivation of Qur'anic morals depends on the integration of collaborative mechanisms that sustain moral habituation across school and home environments.